HOSPITAL SOUNDSCAPE: ACOUSTICS EVALUATION IN NEONATAL INTENSIVE CARE UNIT (NICU) ROOM OF A NATIONAL HOSPITAL IN JAKARTA, INDONESIA (DIMENSI: Journal of Architecture and Built Environment, 2016)
Acoustics comfort in a room is one of the most important building physics aspect that should be observed. in public spaces like hospital, especially in an intensive care unit such as NICU. Researches on the acoustic conditions of NICU in Indonesia are still limited. The acoustical study conducted in this research is using objective, subjective, and simulation methods based on soundscape concept with the concern on the nurse’s perception. This research was conducted at a national hospital in Jakarta. According to National Standardization Agency of Indonesia (SNI) and World Health Organization (WHO), the suitable sound pressure level (SPL) for noise in patient’s room is 35 dBA. From the study, it was found that the equivalent SPL value exceeded the standard. Soundscape in NICU can be improve with the addition of curtain on the incubator’s side, installation of glass partition, and ceiling absorber in the nurse station area. The result of simulation showed that the SPL in the room decreased with average value 8.9 dBA for sound source alarm ventilator and 8.2 dBA for sound source medical officer conversations. And the speech transmission index (STI) increased from “bad” to “good” range became “fair” to “excellent” range.